2018
DOI: 10.2519/jospt.2018.7514
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Outcomes in People With Chronic Ankle Instability: The Ability of Functional Performance Tests to Measure Deficits in Physical Function and Perceived Instability

Abstract: Study Design Laboratory-based, cross-sectional study. Background Functional performance tests (FPTs) assess short bouts of unilateral hops for either distance or speed. More research is needed to identify specific FPTs that may be useful for measuring asymmetry outcomes related to functional performance and perceived instability deficits in individuals with chronic ankle instability (CAI). Objectives To identify FPTs that are sensitive to subjective and objective deficits associated with CAI. Methods Twenty-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…More than 10 variations of the Hop Tests have been developed to evaluate coordination and joint stability 36 39 : Single and Triple Hop Test, 36 39 45 46 Lateral or Side-to-Side Hop Test, 47 48 Crossover Hop for Distance, [45][46][47][48] 6 m Timed Hop, 36 39 45 46 Cross 6 m for Time, 36 39 48 Multiple Hop Test (MHT), [49][50][51][52] Agility Hop Test, 53 30 m Single-Leg Agility Hop Test, 54 Figure-of-8 Test 47 48 55 and Square Hop Test. 55 Depending on the particular hop test, the main variable can either be distance, time or number of errors.…”
Section: Hop Testsmentioning
confidence: 99%
“…More than 10 variations of the Hop Tests have been developed to evaluate coordination and joint stability 36 39 : Single and Triple Hop Test, 36 39 45 46 Lateral or Side-to-Side Hop Test, 47 48 Crossover Hop for Distance, [45][46][47][48] 6 m Timed Hop, 36 39 45 46 Cross 6 m for Time, 36 39 48 Multiple Hop Test (MHT), [49][50][51][52] Agility Hop Test, 53 30 m Single-Leg Agility Hop Test, 54 Figure-of-8 Test 47 48 55 and Square Hop Test. 55 Depending on the particular hop test, the main variable can either be distance, time or number of errors.…”
Section: Hop Testsmentioning
confidence: 99%
“…Therefore, while these results failed to support the findings of previously published literature, as it has been widely accepted that ligamentous and retinacular tissues both have proprioceptive qualities that, when impaired, may play a role in the resulting balance impairments and decreased functional and sport performance. 4,5,9,10) One factor that may help explain these findings is that the YBT was determined to be a reliable measure of single limb stance excursion distances as a dynamic balance test in male collegiate soccer players. 18) The lack of significant differences between and within groups may be attributed to the fact that our sample population is not consistent with an athletic population for which the YBT was validated upon.…”
Section: Discussionmentioning
confidence: 99%
“…
This condition can result in long term functional limitations, such as the inability to perform occupational duties and sporting activities, while also making an individual more susceptible to ankle osteoarthritis, and a diminished quality of life. 4,5) This makes the screening, assessment, and treatment of CAI, and the impairments it creates, a paramount topic for research in the field of rehabilitation science. Dynamic balance deficits in unilateral excursion distances, latency in reaction times, and postural sway are some of the most frequently encountered impairments in the clinical environment for patients affected by CAI.
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Similarly, limb strength asymmetry is a factor in injury recurrence and is often implicated in different lower extremity joint pathologies such as osteoarthritis, ACL injuries, and chronic ankle instability. [4][5][6] Despite many athletes passing return to sport criteria, many often demonstrate persistent limb asymmetry that may increase their risk of reinjury. 7 Furthermore, it has been shown that individuals who have quadriceps strength asymmetry have decreased knee function compared to those with higher symmetry.…”
Section: [Athletic Training and Sports Health Care 2021;13(4):e153-e158]mentioning
confidence: 99%